O klasifikaci samojedských jazyků - Blažek, Václav (2014)
The article is introduced by a survey and discussion of previous models of classification of the Samoyedic languages. The main part is devoted to a new model of classification, based on application of so-called recalibrated glottochronology, including a full documentation of wordlists with etymological remarks, statistics and sources. Finally, the present results are compared with previous models. The article follows the study of Hofírková & Blažek 2012, completing so the Uralic language family, consisting of Finno-Ugric and Samoyedic. The most important result of the present contribution is a dating of disintegration of Samoyedic to the 3rd – 2nd cent. BCE, i. e. between disintegrations of its neighbours, Ob-Ugric around 400 BCE and Turkic around 100 BCE. Applying the cladistic strategy based on average values of percentages expressing mutual relations, in the Samoyedic dialect continuum three primarily parallel branches may be determined: North Samoyedic, Selkup and Sayan Samoyedic. Relatively low scores of Nganasan with all other languages (with exception of Enets) probably indicate an influence of a pre-Samoyedic substratum of the Taimyr Peninsula. On the other hand, it is not excluded that the Sayan Samoyedic branch was secondarily 'formed' thanks to the geographical neighbourhood of Kamasin (& Koibal) and Mator (& Taigi and Karagas). In this case, the idea of Helimski (1982) of four coordinate branches would be confirmed.